Comparison Between Ticagrelor and Clopidogrel in Elderly Patients With an Acute Coronary Syndrome: Insights From the SWEDEHEART Registry. Issue 18 (3rd November 2020) - Szummer, Karolina; Montez-Rath, Maria E.; Alfredsson, Joakim; Erlinge, David; Lindahl, Bertil; Hofmann, Robin; Ravn-Fischer, Annica; Svensson, Per; Jernberg, Tomas
Abstract : Background: The comparative efficacy and safety of ticagrelor versus clopidogrel in older patients with myocardial infarction (MI) has received limited study. Methods: We performed an observational analysis of all patients ≥80 years (n=14 005) who were discharged alive with aspirin combined with either clopidogrel (60.2%) or ticagrelor (39.8%) after a MI between 2010 and 2017 registered in the national registry SWEDEHEART (Swedish Web-System for Enhancement and Development of Evidence-Based Care in Heart Disease Evaluated According to Recommended Therapies). Inverse probability treatment weighting was used in Cox regression models to adjust for differences in demographics, in-hospital therapies, and medications. The primary ischemic outcome (death, MI, or stroke), and bleeding were obtained from national registries at 1 year. A sensitivity analysis in <80-year-old patients was performed. Results: In patients ≥80 years, the incidence of the primary ischemic outcome (hazard ratio [HR], 0.97 [95% CI, 0.88–1.06]) was similar for ticagrelor- and clopidogrel-treated patients. Ticagrelor was associated with a 17% and 48% higher risk of death (HR, 1.17 [95% CI, 1.03–1.32]) and bleeding (HR, 1.48 [95% CI, 1.25–1.76]), but a lower risk of MI (HR, 0.80 [95% CI, 0.70–0.92]) and stroke (HR, 0.72 [95% CI, 0.56–0.93]). In <80-year-old patients, the incidence of the primary ischemic outcome was 17% (HR, 0.83 [95% CI, 0.77–0.89]) lower with ticagrelor. Ticagrelor was associated with 15% (HR, 0.85 [95% CI, 0.76–0.96]) lower risk of death, 32% higher risk of bleeding (HR, 1.32 [95% CI, 1.18–1.47]), but lower risk of MI (HR, 0.82 [95% CI, 0.75–0.91]) and stroke (HR, 0.82 [95% CI, 0.69–0.98]). Conclusions: Ticagrelor use among elderly patients with MI was associated with higher risk of bleeding and death compared with clopidogrel. A randomized study of ticagrelor versus clopidogrel in the elderly is needed. Abstract : Supplemental Digital Content is available in the text.